A novel three-component reaction between isocyanides, alcohols or thiols and elemental sulfur: a mild, catalyst-free approach towards O-thiocarbamates and dithiocarbamates - Németh, András György; Keserű, György Miklós; Ábrányi-Balogh, Péter (Beilstein Journal of Organic Chemistry, 2019)
A new multicomponent reaction has been developed between isocyanides, sulfur and alcohols or thiols under mild reaction conditions to afford O-thiocarbamates and dithiocarbamates in moderate to good yields. The one-pot reaction cascade involves the formation of an isothiocyanate intermediate, thus a catalyst-free synthesis of isothiocyanates, as valuable building blocks from isocyanides and sulfur is proposed, as well. The synthetic procedure suits the demand of a modern organic chemist, as it tolerates a wide range of functional groups, it is atom economic and easily scalable.
Keywords: ditihiocarbamate; elemental sulfur; multicomponent reaction; one-pot; thiocarbamate

(untitled) - Len, C.; Postel, D.; Ronco, G.; Villa, P.; Goubert, C.; Jeufrault, E.; Mathon, B.; Simon, H. (J. Agric. Food Chem., 1997)

(untitled) - Zhou, Y.; Wang, L.; Han, L.; Meng, F.; Yang, C. (Carbohydr. Res., 2009)

(untitled) - Ryder, N. S.; Frank, I.; Dupont, M.-C. (Antimicrob. Agents Chemother., 1986)

(untitled) - Spallarossa, A.; Cesarini, S.; Schenone, S.; Ranise, A. (Arch. Pharm. (Weinheim, Ger.), 2009)

(untitled) - Wood, T. F.; Gardner, J. H. (J. Am. Chem. Soc., 1941)

(untitled) - Lin, G.; Shieh, C.-T.; Ho, H.-C.; Chouhwang, J.-Y.; Lin, W.-Y.; Lu, C.-P. (Biochemistry, 1999)

(untitled) - Cesarini, S.; Spallarossa, A.; Ranise, A.; Fossa, P.; La Colla, P.; Sanna, G.; Collu, G.; Loddo, R. (Bioorg. Med. Chem., 2008)

(untitled) - Cesarini, S.; Spallarossa, A.; Ranise, A.; Bruno, O.; La Colla, P.; Secci, B.; Collu, G.; Loddo, R. (Bioorg. Med. Chem., 2008)

(untitled) - Spallarossa, A.; Cesarini, S.; Ranise, A.; Bruno, O.; Schenone, S.; La Colla, P.; Collu, G.; Sanna, G.; Secci, B.; Loddo, R. (Eur. J. Med. Chem., 2009)

(untitled) - Cichero, E.; Cesarini, S.; Fossa, P.; Spallarossa, A.; Mosti, L. (Eur. J. Med. Chem., 2009)

(untitled) - Spallarossa, A.; Cesarini, S.; Ranise, A.; Schenone, S.; Bruno, O.; Borassi, A.; La Colla, P.; Pezzullo, M.; Sanna, G.; Collu, G.; Secci, B.; Loddo, R. (Eur. J. Med. Chem., 2009)

(untitled) - Zhou, L.; Tan, C. K.; Jiang, X.; Chen, F.; Yeung, Y.-Y. (J. Am. Chem. Soc., 2010)

(untitled) - Tan, C. K.; Zhou, L.; Yeung, Y.-Y. (Org. Lett., 2011)

(untitled) - Zhou, L.; Chen, J.; Tan, C. K.; Yeung, Y.-Y. (J. Am. Chem. Soc., 2011)

(untitled) - Han, W.-Y.; Li, S.-W.; Wu, Z.-J.; Zhang, X.-M.; Yuan, W.-C. (Chem. – Eur. J., 2013)

(untitled) - Tan, C. K.; Er, J. C.; Yeung, Y.-Y. (Tetrahedron Lett., 2014)

(untitled) - Tay, D. W.; Leung, G. Y. C.; Yeung, Y.-Y. (Angew. Chem., Int. Ed., 2014)

(untitled) - Steiger, A. K.; Pardue, S.; Kevil, C. G.; Pluth, M. D. (J. Am. Chem. Soc., 2016)

(untitled) - Yoshida, S.; Hayashi, Y.; Obitsu, K.; Nakamura, A.; Kikuchi, T.; Sawada, T.; Kimura, T.; Takahashi, T.; Mukuta, T. (Org. Process Res. Dev., 2012)

(untitled) - Yadav, J. S.; Goreti, R.; Pabbaraja, S.; Sridhar, B. (Org. Lett., 2013)

(untitled) - Heyns, A. Y.; Carter, G. A.; Rothwell, K.; Wain, R. L. (Ann. Appl. Biol., 1966)

(untitled) - Rafin, C.; Veignie, E.; Sancholle, M.; Postel, D.; Len, C.; Villa, P.; Ronco, G. (J. Agric. Food Chem., 2000)

The Pesticide Manual - MacBean, C. (British Crop Production Council, 2012)

Biomarkers in Toxicology - Gupta, P. K. (Herbicides and fungicides, 2014)

(untitled) - Thind, T. S.; Hollomon, D. W. (Pest Manage. Sci., 2018)

(untitled) - Carta, F.; Aggarwal, M.; Maresca, A.; Scozzafava, A.; McKenna, R.; Masini, E.; Supuran, C. T. (J. Med. Chem., 2012)

U.S. Patent - Schwimmer, A.; Rubin, D. (Method and compositions for inhibiting tumor cell metabolism, 1993)

(untitled) - Boas, U.; Gertz, H.; Christensen, J. B.; Heegaard, P. M. H. (Tetrahedron Lett., 2004)

(untitled) - Hatai, J.; Pal, S.; Jose, G. P.; Bandyopadhyay, S. (Inorg. Chem., 2012)

(untitled) - Konieczna, D. D.; Blanrue, A.; Wilhelm, R. (Z. Naturforsch., B: J. Chem. Sci., 2014)

(untitled) - Seetharamsingh, B.; Ramesh, R.; Dange, S. S.; Khairnar, P. V.; Singhal, S.; Upadhyay, D.; Veeraraghavan, S.; Viswanadha, S.; Vakkalanka, S.; Reddy, D. S. (ACS Med. Chem. Lett., 2015)

(untitled) - Selvakumar, N.; Kumar, G. S.; Malar Azhagan, A.; Govinda Rajulu, G.; Sharma, S.; Kumar, M. S.; Das, J.; Iqbal, J.; Trehan, S. (Eur. J. Med. Chem., 2007)

(untitled) - Sasse, K. (Justus Liebigs Ann. Chem., 1970)

(untitled) - Barma, D. K.; Bandyopadhyay, A.; Capdevila, J. H.; Falck, J. R. (Org. Lett., 2003)

(untitled) - Kojima, M.; Nakamura, Y.; Ishikawa, T.; Takeuchi, S. (Tetrahedron Lett., 2006)

(untitled) - Iwakawa, T.; Tamura, H.; Murabayashi, A.; Hayase, Y. (Chem. Pharm. Bull., 1991)

(untitled) - Koketsu, M.; Otsuka, T.; Ishihara, H. (Phosphorus, Sulfur Silicon Relat. Elem., 2004)

(untitled) - Gromek, S. M.; deMayo, J. A.; Maxwell, A. T.; West, A. M.; Pavlik, C. M.; Zhao, Z.; Li, J.; Wiemer, A. J.; Zweifach, A.; Balunas, M. J. (Bioorg. Med. Chem., 2016)

(untitled) - Schrader, A. M.; Schroll, A. L.; Barany, G. (J. Org. Chem., 2011)

(untitled) - Boeckman, R. K.; Ge, P.; Reed, J. E. (Org. Lett., 2001)

(untitled) - Steiger, A. K.; Zhao, Y.; Choi, W. J.; Crammond, A.; Tillotson, M. R.; Pluth, M. D. (Biochem. Pharmacol., 2018)

(untitled) - Ranu, B. C.; Saha, A.; Banerjee, S. (Eur. J. Org. Chem., 2008)

(untitled) - Safa, K. D.; Tavakkoli Osgoei, S.; Alyari, M. (J. Sulfur Chem., 2014)

(untitled) - Halimehjani, A. Z.; Hooshmand, S. E.; Shamiri, E. V. (Tetrahedron Lett., 2014)

(untitled) - Halimehjani, A. Z.; Martens, J.; Schlüter, T. (Tetrahedron, 2016)

(untitled) - Modarresi-Alam, A. R.; Inaloo, I. D.; Kleinpeter, E. (J. Mol. Struct., 2012)

(untitled) - Tsuji, K.; Nakamura, K.; Konishi, N.; Okumura, H.; Matsuo, M. (Chem. Pharm. Bull., 1992)

(untitled) - Hagooly, Y.; Gatenyo, J.; Hagooly, A.; Rozen, S. (J. Org. Chem., 2009)

(untitled) - Ranade, S. C.; Hasty, S. J.; Demchenko, A. V. (J. Carbohydr. Chem., 2013)

(untitled) - Chniti, I.; Sanhoury, M. A. K.; Chehidi, I. (J. Fluorine Chem., 2013)

(untitled) - Chniti, I.; Sanhoury, M. A. K.; Merlet, D.; Chehidi, I. (J. Fluorine Chem., 2014)

(untitled) - Liu, X.; Wang, Z.; Xie, R.; Tang, P.; Yuan, Q. (Eur. J. Med. Chem., 2018)

(untitled) - Wróblewska, A.; Mlostoń, G. (Phosphorus, Sulfur Silicon Relat. Elem., 2013)

(untitled) - Zhu, J.-B.; Chen, E. Y.-X. (J. Am. Chem. Soc., 2015)

(untitled) - Bassetto, M.; Ferla, S.; Pertusati, F.; Kandil, S.; Westwell, A. D.; Brancale, A.; McGuigan, C. (Eur. J. Med. Chem., 2016)

(untitled) - Cai, W.; Wu, J.; Liu, W.; Xie, Y.; Liu, Y.; Zhang, S.; Xu, W.; Tang, L.; Wang, J.; Zhao, G. (Molecules, 2018)

(untitled) - Larsen, C.; Steliou, K.; Harpp, D. N. (J. Org. Chem., 1978)

(untitled) - Kim, S.; Yi, K. Y. (Tetrahedron Lett., 1985)

(untitled) - Wong, R.; Dolman, S. J. (J. Org. Chem., 2007)

(untitled) - Nath, J.; Ghosh, H.; Yella, R.; Patel, B. K. (Eur. J. Org. Chem., 2009)

(untitled) - Zhang, X.; Lee, Y. K.; Kelley, J. A.; Burke, T. R. (J. Org. Chem., 2000)

(untitled) - Li, Z.-Y.; Ma, H.-Z.; Han, C.; Xi, H.-T.; Meng, Q.; Chen, X.; Sun, X.-Q. (Synthesis, 2013)

(untitled) - Jae Nyoung, K.; Ryu, E. K. (Tetrahedron Lett., 1993)

(untitled) - Kim, J. N.; Jung, K. S.; Lee, H. J.; Son, J. S. (Tetrahedron Lett., 1997)

(untitled) - Baumann, M.; Baxendale, I. R. (Beilstein J. Org. Chem., 2013)

(untitled) - Tanaka, S.; Uemura, S.; Okano, M. (Bull. Chem. Soc. Jpn., 1977)

(untitled) - Bachi, M. D.; Balanov, A.; Bar-Ner, N. (J. Org. Chem., 1994)

(untitled) - Bachi, M. D.; Melman, A. (J. Org. Chem., 1995)

(untitled) - Szabó, T.; Milen, M. (Chem. Heterocycl. Compd., 2019)

(untitled) - Tan, W.; Wei, J.; Jiang, X. (Org. Lett., 2017)

(untitled) - Reiffen, M.; Hoffmann, R. W. (Chem. Ber., 1977)

(untitled) - Cunico, R. F.; Maity, B. C. (Org. Lett., 2003)

(untitled) - Mampuys, P.; Zhu, Y.; Vlaar, T.; Ruijter, E.; Orru, R. V. A.; Maes, B. U. W. (Angew. Chem., Int. Ed., 2014)

(untitled) - Nguyen, T. B.; Ermolenko, L.; Al-Mourabit, A. (Synthesis, 2014)

(untitled) - Pathare, R. S.; Patil, V.; Kaur, H.; Maurya, A. K.; Agnihotri, V. K.; Khan, S.; Devunuri, N.; Sharon, A.; Sawant, D. M. (Org. Biomol. Chem., 2018)

(untitled) - Boyer, J. H.; Ramakrishnan, V. T. (J. Org. Chem., 1972)

(untitled) - Zajdlik, A.; Wang, Z.; Hickey, J. L.; Aman, A.; Schimmer, A. D.; Yudin, A. K. (Angew. Chem., Int. Ed., 2013)

(untitled) - Adam, W.; Bargon, R. M.; Bosio, S. G.; Schenk, W. A.; Stalke, D. (J. Org. Chem., 2002)

(untitled) - Arisawa, M.; Ashikawa, M.; Suwa, A.; Yamaguchi, M. (Tetrahedron Lett., 2005)

(untitled) - Farrell, W. S.; Zavalij, P. Y.; Sita, L. R. (Organometallics, 2016)

(untitled) - Chakrabarty, S.; Choudhary, S.; Doshi, A.; Liu, F.-Q.; Mohan, R.; Ravindra, M. P.; Shah, D.; Yang, X.; Fleming, F. F. (Adv. Synth. Catal., 2014)

(untitled) - Boyarskiy, V. P.; Bokach, N. A.; Luzyanin, K. V.; Kukushkin, V. Y. (Chem. Rev., 2015)

(untitled) - Fujiwara, S.-i.; Shin-Ike, T.; Okada, K.; Aoki, M.; Kambe, N.; Sonoda, N. (Tetrahedron Lett., 1992)

(untitled) - Feng, W.; Zhang, X.-G. (Chem. Commun., 2019)

(untitled) - Milen, M.; Ábrányi-Balogh, P.; Dancsó, A.; Frigyes, D.; Pongó, L.; Keglevich, G. (Tetrahedron Lett., 2013)

(untitled) - Ábrányi-Balogh, P.; Dancsó, A.; Frigyes, D.; Volk, B.; Keglevich, G.; Milen, M. (Tetrahedron, 2014)

(untitled) - Varga, V.; Milen, M.; Ábrányi-Balogh, P. (Tetrahedron Lett., 2018)

(untitled) - Milen, M.; Slégel, P.; Keglevich, P.; Keglevich, G.; Simig, G.; Volk, B. (Tetrahedron Lett., 2015)

(untitled) - Henderson, R. K.; Jiménez-González, C.; Constable, D. J. C.; Alston, S. R.; Inglis, G. G. A.; Fisher, G.; Sherwood, J.; Binks, S. P.; Curzons, A. D. (Green Chem., 2011)

(untitled) - McConvey, I. F.; Woods, D.; Lewis, M.; Gan, Q.; Nancarrow, P. (Org. Process Res. Dev., 2012)

(untitled) - Niknam, K.; Kiasat, A. R.; Kazemi, F.; Hossieni, A. (Phosphorus, Sulfur Silicon Relat. Elem., 2003)

(untitled) - Burrows, A. A.; Hunter, L. (J. Chem. Soc., 1952)

(untitled) - Degani, I.; Fochi, R.; Magistris, C. (Synthesis, 2009)

(untitled) - L’Abbé, G.; Sorgeloos, D.; Toppet, S.; King, G. S. D.; Van Meerwelt, L. (Bull. Soc. Chim. Belg., 1981)

Chin. Patent Appl. - Lijuan, M.; Shubai, L.; Lili, S.; Mengqi, W. (Method for preparing multi-functional sulfide-bonded collaborative antioxidative stabilizer, 2015)

(untitled) - Labib, M. B.; Lamie, P. F. (Med. Chem. Res., 2016)

(untitled) - Nguyen, T. B.; Ermolenko, L.; Retailleau, P.; Al-Mourabit, A. (Angew. Chem., Int. Ed., 2014)

(untitled) - Nguyen, L. A.; Ngo, Q. A.; Retailleau, P.; Nguyen, T. B. (Green Chem., 2017)

(untitled) - Nguyen, T. B.; Retailleau, P. (Org. Lett., 2017)

Organic Chemistry - Clayden, J.; Greeves, N.; Warren, S.; Wothers, P. (Conjugate addition, 2001)

(untitled) - Al-Suwaidan, I. A.; Alanazi, A. M.; Abdel-Aziz, A. A.-M.; Mohamed, M. A.; El-Azab, A. S. (Bioorg. Med. Chem. Lett., 2013)

(untitled) - Jatav, V.; Mishra, P.; Kashaw, S.; Stables, J. P. (Eur. J. Med. Chem., 2008)

(untitled) - Smaill, J. B.; Gonzales, A. J.; Spicer, J. A.; Lee, H.; Reed, J. E.; Sexton, K.; Althaus, I. W.; Zhu, T.; Black, S. L.; Blaser, A.; Denny, W. A.; Ellis, P. A.; et al. (J. Med. Chem., 2016)

(untitled) - Noble, M. E.; Endicott, J. A.; Johnson, L. N. (Science, 2004)

(untitled) - Asagarasu, A.; Matsui, T.; Hayashi, H.; Tamaoki, S.; Yamauchi, Y.; Minato, K.; Sato, M. (J. Med. Chem., 2010)

(untitled) - Sayahi, M. H.; Saghanezhad, S. J.; Bahadorikhalili, S.; Mahdavi, M. (Appl. Organomet. Chem., 2019)

(untitled) - Okamoto, K.; Yamamoto, T.; Kanbara, T. (Synlett, 2007)

(untitled) - Chen, H.-Y.; Peng, W.-T.; Lee, Y.-H.; Chang, Y.-L.; Chen, Y.-J.; Lai, Y.-C.; Jheng, N.-Y.; Chen, H.-Y. (Organometallics, 2013)